Development of Flight Dynamics Model for AH-25 Hybrid Unmanned Aerial Vehicle - Ubadike, Osichinaka C.; Dandago, Khalid K.; Zango, Mahmud S.; Mohammed, Ameer; Okonkwo, Paul P.; Chollom, T. D.; Muhammad, Bashir B.; Adeboye, Christopher O. (Applications of Modelling and Simulation, 2022)
A good mathematical model accurately represents the behavior of a system. Although aircraft has complex dynamics, it is feasible to develop a robust model that could be used to design and analyze some of its essential components such as flight control system and simulator. To solve security challenges in the hinterlands and maritime domains, a hybrid Unmanned Aerial Vehicle (UAV), nicknamed ‘AH-25’, was designed by the Air Force Institute of Technology, Nigeria. In this work, the development of flight dynamics models of the vehicle is presented. The AH-25 UAV has the capability of operating in both fixed-wing and Vertical Take-Off and Landing (VTOL) modes for effective operations on land and maritime spaces. Therefore, models that capture the dynamics of the two distinct modes were obtained. The fixed-wing nonlinear model which was developed from first principle using Newton-Euler method was decoupled, trimmed and linearized to set it in a good shape for critical aircraft systems designs. On the other hand, the multicopter model developed by Beihang flight control group was adapted for modelling the VTOL mode. Simulation results showed that the models’ responses are a replica of the actual aircraft operations. Also, responses of the model to perturbations indicated that it is open-loop stable. Furthermore, the mean performance metrics of the fixed-wing model’s open-loop time response to various inputs were evaluated. The model was found to have a rise time of 2 s, 1.33% steady state error and a settling time of 40 s.